Diagnostic value of serum and tissue eosinophil in diagnosis of asthma among patients with chronic rhinosinusitis - Mat, Che Mohd Hilmi Che (2022)
Background: Chronic rhinosinusitis (CRS) is one of the most common chronic inflammatory diseases of sinonasal mucosa. Asthma among CRS patients is often underdiagnosed and causes management of CRS more challenging. Therefore, using serum and tissue eosinophil as an indicator and prediction of asthma in CRS patients are valuable for further preventing recurrent and increase the effectiveness of treatment for CRS. Objective: To determine the association and diagnostic ability of serum and tissue eosinophils in the diagnosis of asthma among CRS patients. Method: A cross-sectional study was conducted involving 24 CRS patients with and without asthma respectively from the Otorhinolaryngology clinic of two tertiary hospitals located in the East Coast of Peninsular Malaysia. Serum and tissue eosinophils (obtained from nasal polyp) between both groups were compared. Association between serum and tissue eosinophils with asthma evaluated using logistic regression analysis, adjusting for important sociodemographic characteristics. The diagnostic ability of serum and tissue eosinophil was then evaluated by assessing the receiver operating characteristic (ROC) curve. Results: A total of 48 CRS patients with a mean [SD] age of 47.50 [14.99] years were included. Patients with asthma had significantly higher serum [0.48 vs 0.35 x109/L] and tissue eosinophil [100 vs 8.5 per HPF]. Tissue eosinophils were found to be an independent predictor of asthma with adjusted OR=1.05, p<0.001, after adjusting for age and serum eosinophils. The area under the ROC curve for serum eosinophil was 69.0%. At optimal cutoff value (0.375 x109/L), the sensitivity and specificity for serum eosinophil was 75.0% and 70.8%. The area under the ROC curve for tissue eosinophil was 93.4%. At optimal cut-off value (58.0 per HPF), the sensitivity and specificity for tissue eosinophil were 79.2% and 91.7% respectively. Conclusion: A significantly higher level of serum and tissue eosinophil are seen in CRS with asthma. However, there was no correlation between serum and tissue eosinophil in both groups. The CRS patient needs to be screened for asthma if the level of serum eosinophil is more than 0.375 x 109/L and tissue eosinophil more than 58 per HPF.